Organizational justice and its impact on reducing the sense of job burnout - Binwared, Eman Hief Abdullah; Abdalkhair, Asia Yagoub Alhadi (Journal of Economic, Administrative and Legal Sciences, 2022)
The human element is considered one of the most important main resources of the organization, due to its capabilities that create a competitive advantage, but this resource is exposed to many pressures that reflect its commitment to work and threaten the organization and the worker together and due to many reasons, including those related to workers or to the prevailing justice in the organization in which they work, which shows this In the performance of employees, the aim of the research is to identify the reality of organizational justice and to indicate the impact of organizational justice (the justice of procedures, transactions, distributive) on reducing the feeling of job burnout Cov19. The study followed the descriptive analytical approach, and reached several results, including the presence of a statistically significant effect of the dimensions of organizational justice combined in reducing the sense of job burnout among faculty members at King Khalid University under the COV 19 pandemic, and the presence of an average level of job burnout among faculty members under the COV pandemic. 19. The study recommended working on the development and awareness of employees of the importance of organizational justice, which is positively reflected on the overall performance of the organization.